Hubungan pelaksanaan edukasi oleh perawat tentang hand hygiene dengan tingkat pengetahuan keluarga pasien - Sakinah, Aulia; Erianti, Susi; Lita , Lita (Holistik Jurnal Kesehatan, 2025)
Background: Implementing hand hygiene education is an important step in preventing the spread of infection in the hospital environment. The patient's family as companions has a role in maintaining hand hygiene, but the level of knowledge of the patient's family is often still low. This study aims to determine the relationship between the implementation of hand hygiene education and the level of knowledge of patient families. Purpose: To determine the relationship between the implementation of hand hygiene education and the level of knowledge of the patient's family. Method: Quantitative research with a cross-sectional approach, conducted in December 2024 at Arifin Achmad Regional General Hospital, Riau. The sampling technique used purposive sampling with a sample size of 90 respondents. The independent variable in this study was hand hygiene education, while the dependent variable was the level of knowledge. Data analysis used univariate in the form of frequency distribution and bivariate using the chi-square test. Results: The implementation of education went well with 76 (84.45) respondents and had a good level of knowledge with 59 (65.6%) respondents. The statistical test results showed a p-value of 0.225 (>0.05), meaning that there was no significant relationship between the implementation of hand hygiene and the knowledge level of patients' families. Conclusion: There was no significant relationship between the implementation of education by nurses on hand hygiene and the knowledge level of patients' families.   Keywords: Education; Family; Hand Hygiene; Knowledge.   Pendahuluan: Pelaksanaan edukasi hand hygiene merupakan langkah penting dalam mencegah penyebaran infeksi di lingkungan rumah sakit. Keluarga pasien sebagai pendamping memiliki peran dalam menjaga kebersihan tangan, namun tingkat pengetahuan keluarga pasien sering kali masih rendah. Tujuan: Untuk mengetahui hubungan antara pelaksanaan edukasi hand hygiene dengan tingkat pengetahuan keluarga pasien. Metode: Penelitian kuantitatif dengan pendekatan cross sectional, dilaksanakan pada bulan Desember 2024 di RSUD Arifin Achmad, Riau. Teknik pengambilan sampel menggunakan puposive sampling dengan jumlah sampel yang digunakan sebanyak 90 responden. Variabel independent dalam penelitian ini adalah edukasi hand hygiene, sedangkan variabel dependen adalah tingkat pengetahuan. Analisis data yang digunakan univariat dalam bentuk distribusi frekuensi dan bivariat menggunakan uji chi square. Hasil: Pelaksaan edukasi berjalan dengan baik 76 (84.45) dan memiliki tingkat pengetahuan yang baik pula 59 (65.6%). Hasil uji statistik menunjukkan p-value 0.225 (>0.05), artinya tidak terdapat hubungan yang signifikan antara pelaksanaan hand hygiene dengan tingkat pengetahuan keluarga pasien. Simpulan: Tidak ditemukan adanya hubungan yang signifikan antara pelaksanaan edukasi oleh perawat tentang hand hygiene dengan tingkat pengetahuan keluarga pasien.   Kata Kunci: Edukasi; Hand Hygiene; Keluarga; Pengetahuan.